Notes on holotypes of hermit crabs (Decapoda: Anomura: Paguroidea) deposited in the collection of Zoological Museum of RAS (Saint-Petersburg, Russia) with remarks on hermit crab diversity along the Russian coast of the Sea of Japan - Marin, Ivan (Zootaxa, 2016)
The holotype of Clibanarius sachalinicus Kobjakova, 1955 and Clibanarius hirsutimanus Kobjakova, 1971 in the collection of Zoological Institute of Russian Academy of Sciences (Saint-Petersburg, Russia) are examined. As a result, Clibanarius hirsutimanus Kobjakova, 1971 is found to be a species of Areopaguristes nigroapiculus (Komai, 2009) while Clibanarius sachalinicus Kobjakova, 1955 is a species of Clibanarius virescens (Krauss, 1843). Remarks on a single record of Diogenes penicillatus Stimpson, 1858 from Shamora Bay (Usury Bay) of the Sea of Japan as well as current faunal list of hermit crabs from the Russian coasts of the Sea of Japan are also presented in the paper.